MLC901 (NeuroAiD II™) for cognition after traumatic brain injury: a pilot randomized clinical trial - Theadom, A.; Barker‐Collo, S.; Jones, K. M.; Parmar, P.; Bhattacharjee, R.; Feigin, V. L. (European journal of neurology, 2018)
Background and purpose Treatments to facilitate recovery after traumatic brain injury (TBI) are urgently needed. We conducted a 9‐month pilot, randomized placebo‐controlled clinical trial to examine the safety and potential effects of the herbal supplement MLC901 (NeuroAiD II™) on cognitive functioning following TBI. Methods Adults aged 18–65 years at 1–12 months after mild or moderate TBI were randomized to receive MLC901 (0.8 g capsules 3 times daily) or placebo for 6 months. The primary outcome was cognitive functioning as assessed by the CNS Vital Signs online neuropsychological test. Secondary outcomes included the Cognitive Failures Questionnaire, the Rivermead Post‐concussion Symptom Questionnaire (neurobehavioral sequelae), Quality of Life after Brain Injury, Hospital Anxiety and Depression Scale, Modified Fatigue Impact Scale and extended Glasgow Outcome Scale (physical disability). Assessments were completed at baseline and at 3‐, 6‐ and 9‐month follow‐up. Linear mixed‐effects models were conducted, with the primary outcome time‐point of 6 months. Results A total of 78 participants [mean age 37.5 ± 14.8 years, 39 (50%) female] were included in the analysis. Baseline variables were similar between groups (treatment group, n = 36; control group, n = 42). Linear mixed‐effects models controlling for time, group allocation, repeated measurements, adherence and baseline assessment scores revealed significant improvements in complex attention (P = 0.04, d = 0.6) and executive functioning (P = 0.04, d = 0.4) at 6 months in the MLC901 group compared with controls. There were no significant differences between the groups for neurobehavioral sequelae, mood, fatigue, physical disability or overall quality of life at 6 months. No serious adverse events were reported. Conclusions MLC901 was safe and well tolerated post‐TBI. This study provided Class I/II evidence that, for patients with mild to moderate TBI, 6 months of MLC901 improved cognitive functioning.